Analisis Penggunaan Software Microsoft Mathematics 4.0 Dalam Pembelajaran Matematika Di Tingkat Sekolah Menengah Pertama - Hidayah, Taufiq; Asidiq, Sehril (UIN Sunan Gunung Djati Bandung, 2024)
In today's digital era, the use of technology in learning mathematics is becoming increasingly important. the use of ICT will make math learning more interactive by using computer applications. One of the technologies that can be used is math software, such as Microsoft Mathematics 4.0. This software has many functions to solve math problems. This study used a qualitative research method with a qualitative descriptive approach. The study population was class VIII E MTs. Miftahul Falah. The results showed that at the first meeting of the implementation of learning with microsoft mathematics media the percentage of learning was 86.47%, then at the second meeting the percentage was 91.34%, and at the last meeting the percentage was 94.60%. From the observation data, an average of 90.80% was obtained with very good qualifications. In addition, based on the results of interviews, learning by using software media gets a good response from students, they are very enthusiastic about trying and working on problems using software. It can be concluded that Microsoft Mathematics software can be used as a medium for learning mathematics. The research conducted must have many shortcomings, so the advice we can give is to invite further researchers to focus on things that we think can be developed again.